Toward a Modern Chinese Buddhism Taixu's Reforms - Pittman, Don A. (University of Hawaii Press, 2001)
The Venerable Master Taixu (1890-1947) is the most important and controversial Chinese Buddhist reformer of the twentieth century. Viewed as dangerously rash by conservative Buddhists, irrelevant by secular humanists, and spiritually misguided by Christian missionaries, Taixu was nevertheless committed to forging a socially engaged form of Buddhism and to organizing a Buddhist mission in the West. His bold and inventive "Buddhist revolution" continues to shape aspects of a revitalized Buddhism in East Asia and around the world. The present volume is the first major study in English to focus on the charismatic reformer and his teachings and provides a comprehensive and absorbing interpretation of Taixu's aims and the divisive controversies that surrounded him. This nuanced work is richly documented with "ations from Taixu's own writings and from various Chinese intellectuals and evangelists of the period.